ANALISIS WORK-RELATED MUSCULOSKELETAL DISORDERS (WMSDS) PADA OPERATOR MANUFAKTUR ELEKTRONIK DENGAN PENDEKATAN NORDIC BODY MAP (NBM) & QUICK EXPOSURE CHECKLIST (QEC) - Jingga, Nurha Vina; Lawi, Ansarullah; Mardiansyah, Yopy (Universitas Putera Batam, 2025)
This study comprehensively evaluates the risk of Work-Related Musculoskeletal Disorders (WMSDs) among production operators at PT EMS, a company engaged in electronics manufacturing. Utilizing a mixed-methods ergonomic approach, the research employed the Nordic Body Map (NBM) to measure operators' subjective complaint levels and the Quick Exposure Checklist (QEC) to assess objective posture-related exposure risks. Analysis of NBM data revealed that the Printing station exhibited the lowest average complaint levels (5.6 total average complaints per operator), indicating better ergonomic conditions. Conversely, Wave Solder and Cutting Point operators reported the highest average total complaints (11.9 and 11.6, respectively), with the Wave Solder station registering the highest proportion of